Cretaceous/Paleogene Floral Turnover in Patagonia: Drop in Diversity, Low Extinction, and a Classopollis Spike - Barreda, Viviana Dora (2012)
The available information about fossil tetrapods is biased towards their hard parts (i.e., bones and osteoderms) and the interaction of these organisms with the substrate (i.e., tracks). Evidence of biotic interactions between tetrapods and other organisms, particularly other tetrapods, are rarely reported and deciphering such evidence represents a challenge to understanding the fossil record. Evidence such as animal-animal interactions are best interpreted through examination of the ichnological record, which has the potential to elucidate functional aspects of the ecosystem. Actually, bone modification features are capable of revealing the injuries caused by agonistic behavior or predator attack, and also scavenging activities on skeletal remains (e.g., [1]), where bioerosive activity becomes relevant [2]. Surprisingly, although these features are commonly found in the fossil record, they are clearly underrepresented in the scientific literature and, when mentioned, are usually not detailed or figured. During the last few years, a renewed interest in these phenomena has begun to change this situation (e.g., [3,4,5,6]). However, due to differences in the fossil representation or in searching efforts, the vast majority of these reports are often focused on the northern hemisphere (e.g., [1,7,8,9,10,11]), whereas few concern southern hemisphere ecosystems (e.g., [12]). The Upper Cretaceous strata from northern Patagonia, Argentina, have demonstrated an unusual potential for the preservation of large dinosaurs (e.g., [13,14,15]), but also of small and medium-sized tetrapods (e.g., [16,17,18]). The locality known as La Buitrera, located 32 km northwest of Cerro Policıa (Rio Negro Province, Patagonia, Argentina) (Fig. 1), has yielded numerous taxa of mainly ??medium-sized?? tetrapods that preserve superb histological details both in their bone structure and on their surfaces. The early Late Cretaceous sandstones of the Candeleros Formation [19] that outcrop at La Buitrera locality have an excellent preservation potential due to their deposition under brief periods of subaerial exposure, as evidenced by several levels of paleosols as well as abundant bioerosive structures on the surfaces of tetrapod bones. The aim of this contribution is to describe these trace fossils and, when possible, to analyze and interpret the possible tracemakers and consider some insights on the ecological relationships of different components of this Cretaceous ecosystem.